A semi-analytical analysis of strength and critical buckling behavior of underwater ring-stiffened cylindrical shells. (15th January 2021) - Yang, Yang; Li, Jun-Jian; Zhang, Yu; He, Qi; Dai, Hong-Liang
Highlights: Strength and buckling analysis of ring-stiffened cylindrical shell is investigated. Dynamic response of ring-stiffened shell is obtained. Energy method for solving the critical buckling load is considered. Abstract: In this paper, strength and buckling behavior analysis of a ring-stiffened cylindrical shell for the sightseeing submersible subjected to mechanical and thermal loads are studied. Based on the Donnell's assumption and classical shell theory, the governing equations of strength analysis for the ring-stiffened cylindrical shell are established, and the problems are solved by finite difference method (FDM) and Newmark-β method. Meanwhile, the governing equations of buckling behavior for the ring-stiffened cylindrical shell are set up in view of the energy method, which are resolved by the Ritz method. The research shows that the external load has the most significant influence on the strength of ring-stiffened cylindrical shell. Moreover, compared with other factors, the external load has a great influence on its strength, and the effect of shell thickness on the buckling load of ring-stiffened cylindrical shell is most obvious. The research work can provide theoretical basis for the design and optimizing of underwater equipment such as tourist submarines.